Korelasi Internet Gaming Disorder terhadap Kualitas Tidur Mahasiswa Fakultas Kedokteran UKRIDA Tahun Ajaran 2018/2019 - Januwar Lukita; William William; Indriani K Sumadikarya; Flora Rumiati (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2020)
Internet gaming disorder is a form of pathologically continuous internet usage. One of the disadvantages of this disorder is a disruption of sleep quality due to shorter duration of sleep. This study aimed to determine the correlation between internet gaming disorder and sleep quality among students at the Faculty of Medicine, Krida Wacana Christian University. This study is an analytical study with purposive sampling on 88 respondents, consisting of students from 2015, 2016, 2017, and 2018 intakes at the UKRIDA Faculty of Medicine. The Internet Gaming Disorder Short-Scale Form (IGD9S-SF) questionnaire was used to determine the incidence of internet gaming disorder and the Pittsburgh's Sleep Quality Index (PSQI) questionnaire was used to assess the sleep quality among respondents. Data analysis was performed using SPSS version 24. As many as 87% of respondents had poor sleep quality, and among these respondents, 9.1% experienced an internet gaming disorder. In this study internet gaming disorder had a weak correlation with the quality of sleep.